A Review of Research on UAV Remote Sensing Technology - Liu, Cheng (Scientific Journal of Technology, 2026)
In this paper, UAV remote sensing technology is a new spatial information acquisition technology that integrates UAV flight platform, high-sensitivity remote sensing sensors, high-precision navigation control system and intelligent data processing technology. With the core advantages of low-cost deployment, high maneuverability response, and centimeter-level high-resolution imaging, it effectively breaks through the dual limitations of traditional satellite remote sensing in terms of temporal resolution (easily obscured by clouds, long revisit period) and manned aviation remote sensing in terms of operating cost (high equipment maintenance and personnel support costs) and space flexibility (many restrictions on low-altitude flight). Whether it is the rapid capture of disaster images in emergency response, the accurate monitoring of crop growth in the agricultural field, the tracking of pollution sources in ecological environmental protection, and the collection of refined terrain data in urban planning, this technology can obtain dynamic spatial information of the target area in real time with an efficient and flexible operation mode, providing timely and accurate data support for decision-making in various industries, and has become an indispensable key component of the modern spatial information collection system.